2015
DOI: 10.4238/2015.april.10.14
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression analysis of a heat shock protein 90 β isoform gene from the gills of Wuchang bream (Megalobrama amblycephala Yih) subjected to nitrite stress

Abstract: ABSTRACT. Heat shock protein 90 (HSP90), a highly conserved and multi-functional molecular chaperone, plays an essential role in cellular metabolism and stress response. In this study, HSP90 cDNA named MaHSP90 was cloned from Wuchang bream (Megalobrama amblycephala) gills by using rapid amplification of cDNA ends. The fulllength MaHSP90 cDNA is 2674 bp and consists of a 3',5'-untranslated region and a 2250-bp open reading frame encoding a 750-amino acid long protein. Identity analysis revealed that the amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
(40 reference statements)
1
4
1
Order By: Relevance
“…Guo et al (2013) estimated the caspase-3 mRNA level in nitrite-treated Litopenaeus vannamei and found nitrite led to activation of caspases and initiation of hemocytes apoptosis. In vivo study showed that nitrite exposure induced increases in mRNA levels of caspase -8 and caspase -9 in the gills of juvenile Megalobrama amblycephala (Sun et al, 2014b). In the present study, we also discovered the ascensions in mRNA levels of caspases -3, -7, and -9 in gills of turbot exposed to nitrite.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Guo et al (2013) estimated the caspase-3 mRNA level in nitrite-treated Litopenaeus vannamei and found nitrite led to activation of caspases and initiation of hemocytes apoptosis. In vivo study showed that nitrite exposure induced increases in mRNA levels of caspase -8 and caspase -9 in the gills of juvenile Megalobrama amblycephala (Sun et al, 2014b). In the present study, we also discovered the ascensions in mRNA levels of caspases -3, -7, and -9 in gills of turbot exposed to nitrite.…”
Section: Discussionsupporting
confidence: 62%
“…In aquatic animal, nitrite exposure also promoted apoptosis. Sun et al (2014b) reported that nitrite exposure induced the transcription of apoptosis-related genes (caspase-8 and caspase-9) and contributed to apoptosis in gills of juvenile Megalobrama amblycephala. Similarly, nitrite-induced haemocyte apoptosis was observed in Litopenaeus vannamei, Penaeus monodon and Macrobrachium rosenbergii (Guo et al, 2013;Xian et al, 2011;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Evidences indicate that necrosis is the main cell death program triggered when ATP levels drop rapidly after NO 2 -stress (Leist et al 1997, Brown and Borutaite 2002, Leist et al 1999). In opposition to other studies, few cells were demised from epithelia by apoptosis, however, this cell death program has been reported after NO 2 -intoxication in fish (Jia et al 2015, Sun et al 2014.…”
Section: Discussioncontrasting
confidence: 47%
“…LGTIA(K/R)SGT, IGQFGVGFYS(A/C)(Y/F)LVA(E/D), IKLYVRRVFI and GVVDS(E/D)DLPLN(I/V)SER. Many other studies have also confirmed these signature sequences in insects (Hai-Hong et al, 2014;Chen et al, 2014;Sun et al, 2015;Qiao et al, 2015). Moreover, the two conserved motifs MEEVD in the C-terminal part and the central domain GXXGXG in all HSP90 are also common in HSP70 (Gupta, 1995).…”
Section: Discussionmentioning
confidence: 72%
“…HSP90 proteins are among the most abundant and well-conserved proteins, corresponding to 1-2% of the total proteins in a cell under normal conditions (Sun et al, 2015;Qiao et al, 2015;Lu et al, 2016). HSP90 has an important role in cell homeostasis, acting in fundamental cell activities, such as protein folding and refolding and thermal shock stress as well as other physiological functions, such as cell signaling and protein degradation (Sun et al, 2015;Lu et al, 2016).HSP90 presents two isoforms in the cell: an inducible form (HSP90A) and a constitutive form (HSP90Beta) (Sun et al, 2015). However, only one isoform is present in many insect species (Lu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%